My Storm : Managing the Recovery of New Orleans in the Wake of Katrina - Blakely, Edward J. (Edward James), 1938- (City in the twenty-first century book series., 2012)
My Storm is a firsthand account of a critical sixteen months in the post-Katrina recovery process. It tells how Blakely, as Katrina recovery czar, endeavored to transform the shell of a cherished American city into a city that could not only survive but thrive.